El uso de los recursos didácticos en el aprendizaje de los alumnos del primer año de Educación General Básica de la Escuela de Educación Básica “Eugenio Espejo”, del cantón Baba, provincia Los Ríos. - Murillo Gonzabay, Eloisa M. (2015)
Labor to educate boys and girls, is a process that takes time, effort, dedication, endurance, strength and a lot of love; and, This process requires multiple resources that contribute to achieve the objectives in curriculum planning. All teachers when dealing with the delivery of class one must select the resources and materials you plan to use. Many think it does not matter or material resources because the important thing is to choose the kind But they are wrong, is essential adequately Select Resources and materials Because constitute fundamental to the development and enrichment of the Teaching-Learning Process of Tools Students. Nowadays there are excellent instructional materials that can help the UN provide a teaching class, or you can serve it better support them in their work. These teaching materials can be selected from a lot of them, from those made by publishers or those with experience Self Comes to make. As to the teaching resources, its concept and use, have evolved throughout history mainly as a result of the emergence of new technologies. This research work was determined that Improve Teaching resources allow labor of teachers in their practice and also contribute to the development of meaningful learning in children from the School of Basic Education "Eugenio Espejo" Baba Canton, province from The Rivers.